Peningkatan Kualitas Layanan Publik Melalu Pendataan Infrastruktur di Desa Lamabelawa - Thomas Raymonddino Selo; Krisantus Simon H Molan; Stephanie Perdana Ayu Lawalu (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The devotion found a problem namely infrastructure data collection activities which are an important aspect in efforts to improve development in the village are not carried out regularly or there is no updating of data related to new infrastructure. The purpose of the activity carried out by the devotion is to assist in improving the quality of public services and as a benchmark in making policies related to infrastructure development in Lamabelawa village. The methods used in this activity are observation and interview. The result of this activity is that the village government can improve public services through infrastructure data collection which can help the village government in ensuring that development policies taken are in accordance with conditions and needs, providing maximum benefits for the Lamabelawa village community. Regular data collection can help the village government and the community to know the needs and conditions of infrastructure in the village.